Nutritional, Health, and Technological Functionality of Lupin Flour Addition to Bread and Other Baked Products: Benefits and Challenges - Villarino, C.; Jayasena, Vijay; Coorey, Ranil; Chakrabarti-Bell, S.; Johnson, Stuart (Taylor and Francis LTD, 2016)
Lupin is an undervalued legume despite its high protein and dietary fiber content and potential health benefits. This review focuses on the nutritional value, health benefits, and technological effects of incorporating lupin flour into wheat-based bread. Results of clinical studies suggest that consuming lupin compared to wheat bread and other baked products reduce chronic disease risk markers; possibly due to increased protein and dietary fiber and bioactive compounds. However, lupin protein allergy has also been recorded. Bread quality has been improved when 10% lupin flour is substituted for refined wheat flour; possibly due to lupin-wheat protein cross-linking assisting bread volume and the high water-binding capacity (WBC) of lupin fiber delaying staling. Above 10% substitution appears to reduce bread quality due to lupin proteins low elasticity and the high WBC of its dietary fiber interrupting gluten network development. Gaps in understanding of the role of lupin flour in bread quality include the optimal formulation and processing conditions to maximize lupin incorporation, role of protein cross-linking, antistaling functionality, and bioactivity of its γ-conglutin protein.